(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
In the long history of cultural relations between Constantinople and Venice we can note a certain curiosity for Ottoman music, evident in the observations written by the Venetian ambassador (bailo) Giovanbattista Donado (1627-1699) in his Della Letteratura de’ Turchi (1688), and, one century later, by an entire and detailed chapter on Ottoman music written by Venetian Jesuit abbot Giambattista Toderini (1728-1799) in his Letteratura Turchesca (1787). This curiosity can be intended as an ideal aesthetic background for the present Bîrûn, the seminar of higher education in Ottoman classical music directed by Kudsi Erguner, which begun in 2012 at the Institute for Comparative Music Studies (IISMC) of the Giorgio Cini Foundation, in cooperation with the Department of Philosophy and Cultural Heritage (DFBC) of the Venice University ‘Ca’ Foscari’. The large number of applications received and the presence of many young and talented musicians from all over the world shows the vitality of Ottoman classical music.